Inflammatory Cell-Targeted Delivery Systems for Myocardial Infarction Treatment - Wenyuan Zhang; Dan Peng; Shiqi Cheng; Rui Ni; Meiyang Yang; Yongqing Cai; Jianhong Chen; Fang Liu; Yao Liu (Bioengineering)
Myocardial infarction (MI) is a cardiovascular disease (CVD) with high morbidity and mortality worldwide, which is a serious threat to human life and health. Inflammatory and immune responses are initiated immediately after MI, and unbalanced inflammation post-MI can lead to cardiac dysfunction, scarring, and ventricular remodeling, emphasizing the critical need for an effective inflammation-regulating treatment. With the development of novel therapies, the drug delivery system specific to inflammatory cells offers significant potential. In this review, we introduce immune cells and fibroblasts involved in the development of MI and summarize the newly developed delivery systems related to the use of injectable hydrogels, cardiac patches, nanoparticles, and extracellular vesicles (EVs). Finally, we highlight the recent trends in the use of inflammatory cell-targeting drug delivery systems involving different strategies that facilitate the effective treatment of MI.